Isolation of anticancer bioactive secondary metabolites from the sponge-derived endophytic fungi Penicillium sp. and in-silico computational docking approach - Kaliaperumal, Kumaravel; Salendra, Limbadri; Liu, Yonghong; Ju, Zhiran; Sahu, Sunil Kumar; Elumalai, Sanniyasi; Subramanian, Kumaran; M. Alotaibi, Nahaa; Alshammari, Nawaf; Saeed, Mohd; Karunakaran, Rohini (Frontiers in Microbiology, 2023)
Fungal secondary metabolites are the diverse group of natural chemical products with biomedical relevance. An organic ethyl acetate extract of Penicillium verruculosum a sponge derived endophytic fungi from Spongia officinalis yielded seven different secondary metabolites Averufin (1), Aspergilol-A (2), Sulochrin (3), Monomethyl Sulochrin (4), Methyl Emodin (5), Citreorosein (6), diorcinol (7). All the seven isolated compounds were characterized by NMR spectral studies. All the seven compounds were subjected for bioactivity screening like anticancer, antimicrobial, anti-tuberculosis and antiviral. Among those, averufin (1), shows strong anticancer activity towards human HL60 cell lines with the IC50 concentration of 1.005 (µm), as plausible to that of standard anticancer drug Taxol. Consecutive molecular docking approach of Averufin (1) with HL60 antigens revealed that target bindings of Averufin (1) with the HL60 antigens are very strong enough with good pharmacokinetic properties. As we conclude that Averufin (1) isolated from Penicillium verruculosum can be taken for further preliminary clinical trials like animal model In-vivo studies and pharmacodymanic studies. Furthermore Aspergilol-A (2) is the first time report from Penicillium verruculosum fungal strain.